Tracing Rhetoric and Material Life Ecological Approaches (Palgrave Studies in Media and Environmental Communication, 2018)
This volume brings together three areas of scholarship and practice: rhetoric, material life, and ecology. The chapters build a multi-layered understanding of material life by gathering scholars from varied theoretical and critical traditions around the common theme of ecology. Emphasizing relationality, connectedness and context, the ecological orientation we build informs both rhetorical theory and environmentalist interventions. Contributors offer practical-theoretical inquiries into several areas - rhetoric's cosmologies, the trophe, bioregional rhetoric's, nuclear colonialism, and more - collectively forging new avenues of communication among scholars in environmental communication, communication studies, and rhetoric and composition. This book aims at inspiring and advancing ecological thinking, demonstrating its value for rhetoric and communication as well as for environmental thought and action.